More than a Storm in a Teacup? British Nationals in Poland in the Time of Brexit - Stephen Davies (Ksiegarnia Akademicka Publishing, 2021)
The paper will present and analyse the results of qualitative research conducted by Stephen Davies with British nationals residing in Poland. The research questions explore their attitudes towards Britain and Brexit, as well as their future plans connected with their place of residence. The dominant themes of the paper are the questions of belonging and attachment. The analysis is preceded by a short introductory section which presents the context of the Brexit processes, as well as the results of research into EU migrants in the United Kingdom and British nationals living in different parts of the European Union.